PENGARUH PEMBERIAN LIMBAH CAIR BIOGAS TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq. ) DI MAIN NURSERY - Matdalena, Matdalena; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aimed to determine the effect of giving bioslurry and get a dose of the best on the growth oil palm seedlings (Elaeis guineensis jacq.) in main nursery. This research has been conducted in the experimental field of the Agriculture Faculty, University of Riau from Agustus 2015 until the month of Januari 2016. The research was conducted by using a Completely Randomized Design (CRD), consisted of 6 treatments and 4 replications. The treatment is bioslurry, B1= 0 ml, B2=100 ml, B3= 200 ml, B4= 300 ml, B5= 400 ml, dan B6= 500 ml. Parameters that observed were seedling height, the increase of hump diameter, the increase of leaf number an leaf area. Data were analyzed by analysis of variance, then continued with further test with Duncan's new multiple range test at 5%. The results of research of bioslurry no significantly effect to seedlings height, the increase of leaf number, the increase of hump diameter, an leaf area. Provision of bioslurry of 300 ml is the best treatment against the of seedling height is 30,43 cm, the increase of hump diameter 2,40 cm, the increase of leaf number 7,50 sheet an leaf area 277,08 cm2 an compared with no provision of bioslurry to seedling height 17,84%, the increase of hump diameter 27,91%, the increase of leaf number 21,73% an leaf area 16,29%. Keywords: bioslurry, oil palm seedlings, growth, main nursery.